Associations between Adolescents' Social Leisure Activities and the Onset of Mental Disorders in Young Adulthood. - Timonen, Johanna; Niemelä, Mika; Hakko, Helinä; Alakokkare, Anni; Räsänen, Sami (Journal of Youth & Adolescence, 2021)
The association of leisure time activities with specific mental disorders has mainly remained unclear because of lack of such research. This study analyzed the association of different levels of social leisure time activity during adolescence (ages 15–16 years) with the incidence of mental disorders during adolescence and young adulthood between the ages of 16–33 years. The study population consisted of 6838 (females 51.5%) participants from the longitudinal follow-up study, the Northern Finland Birth Cohort 1986, covering 72% of the total 1986 birth cohort. Psychiatric morbidity of the participants was followed through nationwide health registers until the end of the year 2018 when the participants were 33 years old. High social leisure time activity in adolescence associated with lower incidence of psychiatric disorders in general, and specifically, with affective, anxiety, and substance use disorders. Low social leisure time activity was related to increased incidence of any psychiatric disorder in general, and particularly to anxiety and behavioral disorders. In terms of prevention of mental disorders, these study findings encourage families, schools and other communities to continue to enhance and develop community-based social leisure time activities for children and adolescents.